Antioxidant Activities of Natural Polysaccharides and Their Derivatives for Biomedical and Medicinal Applications - Lu Bai; Dong Xu; Yan-Ming Zhou; Yong-Bo Zhang; Han Zhang; Yi-Bing Chen; Yuan-Lu Cui (MDPI AG, 2022)
Many chronic diseases such as Alzheimer's disease, diabetes, and cardiovascular diseases are closely related to in vivo oxidative stress caused by excessive reactive oxygen species (ROS). Natural polysaccharides, as a kind of biomacromolecule with good biocompatibility, have been widely used in biomedical and medicinal applications due to their superior antioxidant properties. In this review, scientometric analysis of the highly cited papers in the Web of Science (WOS) database finds that antioxidant activity is the most widely studied and popular among pharmacological effects of natural polysaccharides. The antioxidant mechanisms of natural polysaccharides mainly contain the regulation of signal transduction pathways, the activation of enzymes, and the scavenging of free radicals. We continuously discuss the antioxidant activities of natural polysaccharides and their derivatives. At the same time, we summarize their applications in the field of pharmaceutics/drug delivery, tissue engineering, and antimicrobial food additives/packaging materials. Overall, this review provides up-to-date information for the further development and application of natural polysaccharides with antioxidant activities.